REGISTERED vs. UNREGISTERED TRADE MARKS IN THE EUROPEAN UNION - George-Mihai IRIMESCU (Challenges of the Knowledge Society)
This paper aims at analyzing the possibilities of protection of unregistered trademarks in the European Union. Although the European legislation mainly focuses on the protection of registered trademarks, specific provisions provide for the opposabiity of unregistered trademarks that are protected according to the national legislation. The first chapter analyzes the relevant legal provisions, highlighting the European legislator's approach with respect to the protection of unregistered trademarks, from the perspective of the applicable regulations and directives. Then, the main provisions regarding the opposability of national unregistered marks at European level and the conditions they have to meet are also analyzed, also reviewing the relevant case-law. The paper focuses on fulfilling the condition of use, which must meet both the criteria set by the national legistaion and the „Europena criteria”. The notion of „use in the course of trade” is also analysed from the perspective of the applicable case-law. Moving further, the article continues with short considerations on the opposability of well-known trademarks at European level, and, more specifically, regarding the opposability of unregistered trademarks by Romanian holders. Last but not least, the protection of trademarks with reputation is briefly analysed. In conclusion, the paper raises the question wether protection of European unregistred trademarks should concern the European legislator in future amendment of the EU Trade Mark Regulation.